AB1167 Autoreactive T cells to citrullinated HSP90 in interstitial lung disease in rheumatoid arthritis. (15th June 2017) - Chen, J; Song, S; Liu, Y; Liu, D; Ge, S; Ascherman, D
Abstract : Background: Previous studies have indicated that anti-citrullinated protein antibody (ACPAs) titers are associated with the presence and severity of interstitial lung disease (ILD) in RA. The lung might be a site of initiation of immunity to citrullinated proteins. Previous studying anti-citrullinated HSP90 (citHSP90β) profiles between bronchial veolarlavage fluid (BALF) and serum indicated the lung plays a direct role in shaping the immune repertoire of RA-ILD. Objectives: Whether citHSP90β contributes to the initiation or perpetuation of autoimmune interstitial lung abnormalities (ILA) in RA remains to be clarified. To address this issue we investigated the spontaneous T cell responses to the putative autoantigen citrullinated HSP90β in different stages of RA-ILD. Methods: In RA-no ILD (n=19), indeterminate ILD (ILA1) (n=24), subclinical RA-ILD (ILA 2) (n=20), clinical RA-ILD (ILA3) (n=4) and other connective tissue disease associated ILD (CTD-ILD) (n=14) patients. Cultures derived from whole blood were individually stimulated with HSP90β, citHSP90β, citrullinated BSA, or no antigen. The concentration of 13 cytokines and chemokines in the plasma supernatant were then measured using Luminex xMAP technology. Results: CitHSP90β induced significantly higher levels of IFN-γ levels in RA-ILD (ILA=2+3) groups compared to the RA-no ILD group ( p =0.002), but did not stimulate the production of other cytokines ( p >0.05). Furthermore, citHSP90β did not stimulate the production of IFN-γ or other cytokines stimulated those individuals with non-RA CTD-ILD ( p =0.1039, IFN-g). Conclusions: The production of IFN-γ by T cells stimulated with citHSP90b demonstrates a bias toward TH1 immune responses that are likely involved in the pathogenesis of RA-ILD. The presence of autoreactive Th1-like cells in RA patients in conjunction with citrullinated autoantigens may indicate the involvement of this autoantigen in the pathogenesis of RA-ILD. Early targeting of the immune reactions in the lung might therefore be a new approach to modulate disease. References: Chen J, Doyle TJ, Liu Y, Aggarwal R, Wang X, Shi Y, et al. Biomarkers of rheumatoid arthritis-associated interstitial lung disease. Arthritis & rheumatology. 2015; 67:28–38. Harlow L, Rosas IO, Gochuico BR, Mikuls TR, Dellaripa PF, Oddis CV, et al. Identification of citrullinated hsp90 isoforms as novel autoantigens in rheumatoid arthritis-associated interstitial lung disease. Arthritis and rheumatism. 2013; 65:869–79. Bongartz T, Cantaert T, Atkins SR, Harle P, Myers JL, Turesson C, et al. Citrullination in extra-articular manifestations of rheumatoid arthritis. Rheumatology (Oxford). 2007; 46:70–5. Nijenhuis S, Zendman AJ, Vossenaar ER, Pruijn GJ, vanVenrooij WJ. Autoantibodies to citrullinated proteins in rheumatoid arthritis: clinical performance and biochemical aspects of an RA-specific marker. Clinica chimica acta; international journal of clinical chemistry. 2004; 350:17–34. Disclosure of Interest: None declared